AKURASI SKOR RISIKO KILLIP SEBAGAI PREDIKTOR PROGNOSIS PASIEN SINDROM KORONER AKUT ST-ELEVATION MYOCARD INFARCTION - Roesardhyati, Ratna; Wihastuti, Titin Andri; Nasution, Tina Handayani (Jurnal Kesehatan Mesencephalon, 2018)
Abstract : Acute Coronary Syndrome (ACS) with ST-ELevation Myocard Infarction (STEMI) is the leading cause of morbidity and mortality worldwide, especially in developed countries. Many risk factors in ACS patients require long treatment and focused treatment. Stratification of risks plays an important role in assisting prediction of clinical outcomes or as a prognosis in patients with ACS.The prognosis of STEMI patients is indicated by Length of Stay (LOS) which is the number of days of STEMI patient care at ICCU. Currently there is risk score used as predictors in SKA with STEMI, some of which is Killip. This riset to analyze accuracy of Killip risk score with prognosis (LOS) STEMI patient in ICCU dr. Iskak Tulungagung. The research design used was analytic observational research with retrospective cohort approach. The location of this study was in RSUD dr. Iskak Tulungagung. The number of medical record were 125 taken by using purposive sampling technique. Data was analyzed using Spearman test.The result of Spearman test showed that Killip showed a significant association with STEMI patients LOS in ICCU (p = 0.003) with coefficient correlation r = 0.260.The conclusion in this study was that Killip had a significant relationship with the prognosis (LOS) of STEMI patients in ICCU. Keyword : ST-Elevation Myocard Infarction, Killip, Length of Stay Abstract : Sindrom Koroner Akut (SKA) dengan ST-Elevation Myocard Infarction (STEMI)merupakan penyebab utama morbiditas dan mortalitas di seluruh dunia, terutama di negara-negara maju. Faktor risiko yang begitu banyak pada pasien SKA membutuhkan perawatan yang lama dan pengobatan yang terfokus. Stratifikasi risiko tersebut berperan penting dalam membantu prediksi luaran klinis atau sebagai prognosis pada pasien SKA. Prognosis pasien STEMI ditunjukkan dengan Length of Stay (LOS) yang merupakan jumlah hari lama rawat pasien STEMI di ICCU. Saat ini terdapat skor risiko yang digunakan sebagai prediktor pada SKA dengan STEMI, yaituKillip. Tujuan penelitian ini untuk mengalisis akurasi skor risiko Killip dengan prognosis (LOS) pasien STEMI di ICCU RSUD dr. Iskak Tulungagung. Desain penelitian yang digunakan adalah penelitian observasional analitik dengan pendekatan kohort retrospektif. Lokasi penelitian di Intalasi Rekam Medis RSUD dr. Iskak Tulungagung. Jumlah rekam medis sebanyak 125 yang diambil dengan teknik purposive sampling. Analisa data menggunakan uji Spearman. Hasil uji Spearman menunjukkan bahwa Killip menunjukkan hubungan yang signifikan dengan LOS pasien STEMI di ICCU (p=0.003) dengan besar korelasi r=0.260. Kesimpulan dalam penelitian ini adalah skor risiko Killip memiliki hubungan signifikan dengan prognosis (LOS) pasien STEMI di ICCU. Kata Kunci : ST-Elevation Myocard Infarction, Killip, Length of Stay